Lessons learned from investigator‐initiated clinical trials for localized pancreatic cancer. Issue 1 (13th December 2021) - Tsai, Susan; Evans, Douglas B.
Abstract: Investigator‐initiated trials (IITs) are clinical trials in which the clinician is both the sponsor and the investigator. IITs have also been developed to test strategies designed to optimize existing therapies or treatment approaches that may not be supported by industry sponsors or may be too novel to gain the consensus to be supported by cooperative groups. The role of the investigator is comprehensive and includes protocol development, securing funding for the administration of the trial, recruitment and monitoring of subjects, and assurance for the protection of human subjects. We will briefly review the importance of surgeons in developing IITs and provide insights into logistical barriers from conception to completion of the trial. Highlights: 1. Investigator‐initiated trials (IITs) often represent the most innovative clinical trials being conducted and are an opportunity for patients to receive the most groundbreaking therapies. 2. Protocol development should include careful consideration of eligibility criteria to minimize selection bias and maximize accrual. 3. Although administrative costs for IITs are lower than that of industry‐sponsored trials, per‐patient costs are still significant. 4. In oncology, neoadjuvant IITs provide a unique opportunity to further understand cancer biology and are ideal for surgeon‐led trials.